Justice Is Not Blind: A Preliminary Evaluation of an Implicit Bias Training for Justice Professionals - Fix, Rebecca L. (Race and social problems, 2020)
While there are several studies that have tested efficacy of implicit bias trainings, none have tested how working within a justice profession or how one’s racial identity impact outcomes following participation in such a training. Additionally, though empathy influences bias, no studies have tested for the effect of implicit bias training on ethnocultural empathy. The present study is a program evaluation of an implicit bias training program that examines the effects of profession and racial identity on outcomes, including ethnocultural empathy. The implicit bias training was a 3-h standardized training that described how implicit biases are formed, how they impact children in the school-to-prison pipeline and adults in society, the short- and long-term consequences of those biases, and strategies for responding to one’s own implicit biases. Participants who completed implicit bias trainings were 243 justice professionals and 274 non-justice professionals. Results indicated training outcomes were significantly associated with participant gender, race, racial identity, and whether participants worked in justice or non-justice professions. In addition, participants indicated several strengths and assets of the program; how receptive participants were to implicit bias training components was significantly associated with gender, race, and whether the participants worked in justice settings. The current study provides a necessary but incomplete picture of the strengths and weaknesses of this implicit bias training, lending support for continued trainings with more in-depth and longitudinal study of them.